NILAI, ETIKA, DAN TUJUAN PENDIDIKAN ISLAM: ANALISIS AKSIOLOGIS DALAM PENGEMBANGAN TEORI MANAJEMEN PENDIDIKAN - Ahmad Muqaffi; Kautsar Eka Wardhana; Yusnia Binti Kholifah (STKIP Subang, 2025)
Islamic education is a process of forming a complete human being based on values and ethics as its philosophical foundation. However, the development of modern educational management theory, which is oriented toward instrumental rationality, efficiency, and performance achievement, often raises axiological problems when applied in the context of Islamic education. This article aims to conceptually analyze the relationship between values, ethics, and the objectives of Islamic education from an axiological perspective, as well as its implications for the development of educational management theory. This study uses a qualitative approach with a library research method through critical analysis of the literature on Islamic educational philosophy, educational management theory, and the thoughts of Islamic scholars. The results of the study show that tauhid (monotheism) is the highest value that inspires all activities in education and Islamic educational management. Ethical values such as trustworthiness, justice, responsibility, and and the public interest becomes the basis for managerial decision-making, while instrumental values are subordinate to transcendental values. The reconstruction of educational management functions based on axiology requires the integration of Islamic values in planning, organizing, implementation, and supervision. This approach has implications for formulating holistic Islamic education goals, not only oriented towards academic achievement but also toward shaping individuals who are faithful, knowledgeable, and of noble character. Thus, axiology-based educational management is a strategic necessity in maintaining the identity and relevance of Islamic education in the modern era.